Everything is interrelated: Christianity Trinity and Hindu Advaita as experienced by Raimundo Panikkar and Francis Dsa SJ - kuruvilla Pandikattu Ed; PANDIKATTU (Kuruvilla) Ed (Delhi Jnana Deepa Vidyapeeth, 2019)
This book explores the Cosmotheandric vision as proposed by the Indian-Spanish mystic Raimundo Panikkar and interpreted by the Indian thinker Francis DSa SJ.
Keywords: Cosmotheandric Experience; Tempiternity